Comparison of gingival blood flow during healing of simplified papilla preservation and modified Widman flap surgery: a clinical trial using laser Doppler flowmetry - M. Retzepi (Blackwell Synergy, 2007)
Aim: This prospective randomized-controlled clinical trial compared the gingival blood flow responses following simplified papilla preservation (test) versus modified Widman flap (control). Materials and Methods: Twenty contra-lateral upper sites with pocket depthX5mm after initial treatment in 10 chronic periodontitis patients were randomly assigned to either test or control treatment, using a split-mouth design. Laser Doppler flowmetry recordings were performed pre-operatively, following anaesthesia, immediately postoperatively and on days 1, 2, 3, 4, 7, 15, 30 and 60, at nine selected sites per flap. Results: Significant ischaemia was observed at all sites following anaesthesia and immediately post-operatively. At the mucosal flap basis, a peak hyperaemic response was observed on day 1, which tended to resolve by day 4 at the test sites, but persisted until day 7 at the control sites. The buccal and palatal papillae blood perfusion presented the maximum increase on day 7 in both groups and returned to baseline by day 15. Both surgical modalities yielded significant pocket depth reduction, recession increase and clinical attachment gain. Conclusions: Periodontal access flaps represent an ischaemia–reperfusion flap model. The simplified papilla preservation flap may be associated with faster recovery of the gingival blood flow post-operatively compared with the modified Widman flap.